A Dedication of Machine Learning for Trend of Digital HRM - Dasmadi Dasmadi (Postgraduate, University of Mataram, 2023)
The digital world has inevitably entered various fields of human life in carrying out their duties as world leaders. Technology is an important tool to ease the human workload, including in this discourse is human resource management. Machine Learning is a technology that allows machines to learn and adapt quickly from given data without having to be explicitly programmed. Machine Learning has found its place in many industries and has great potential to improve the efficiency of human resources within organizations. This research is a literature review of several articles related to machine learning. The review was conducted from some of the recent research efforts that utilize machine learning. Furthermore, this review is derived from multiple literacies and includes an attempt at problem solving efforts that are divided into section areas from the perspective of each machine learning category. Machine learning can change the way the human resource management domain functions in an organization. It is making changes in all aspects of human resource management starting from human resource planning. Enormous data is available in human resource information systems (HRIS) available in organizations.